Stroke-coordination and symmetry of elite backstroke swimmers using a comparison between net drag force and timing protocols - Formosa, D. P.; Sayers, M. G. L.; Burkett, B. (Journal of Sports Sciences, 2014)
Stroke-coordination and symmetry influence the force fluctuations within any net drag force profile. The aim of this study was to analyse elite (FINA points 938) backstroke swimmers stroke-coordination using an instantaneous net drag force and timing protocols using a symmetry index tool. Ten male and nine female elite backstroke swimmers completed three maximum speed trials and five maximum speed net drag force swimming trials. Net drag force was measured using an assisted motorised dynamometer device. Each trial was filmed using three genlocked 50 Hz cameras, synchronised to the net drag force output from the force-platform. This methodology enabled the comparison of stroke-coordination timing symmetry index to net drag force symmetry index. The timing symmetry index and net drag force symmetry index yielded different results, the timing reflects the stroke-coordination, whilst the force index identified the effectiveness of the stroke. The only variable that was significantly different when comparing left and right stroke patterns was the location of minimum net drag forces. Conversely, gender influenced the location of maximum net drag force. Relationship analysis identified that location of maximum net drag force production was the only variable to correlate with speed within this cohort. Backstroke arm coordination was minimally influenced by gender.